Mathematical reasoning abilities: The Impact of Novick's Learning and Somatic, Auditory, Visual, Intellectual Learning Styles - Yasin, Muhamad; Nasiroh, Nasiroh; Fadila, Abi; Hartinah, Sitti; Novalia, Novalia (Universitas Islam Negeri Raden Intan Lampung, 2020)
Every life needs a very important role especially the role in education. Improving the quality of education can be pursued by the use of appropriate learning models so as to improve students' reasoning abilities. The purpose of this study was to determine the differences in the influence of Novick's learning model and the learning model that is centered on educators on students' mathematical reasoning abilities, Knowing the interaction between learning models and SAVI learning styles (Somatic, Auditory, Visualization, Intelectually) on mathematical reasoning abilities learners. This research uses the Quasy Experiment Design method. The results obtained from this study are that learning by using Novick's learning model is more effective against mathematical reasoning for students, there is no interaction between Novick's learning model and SAVI learning style on mathematical reasoning abilities.